2018
DOI: 10.1007/978-3-319-72026-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Disaster Risk Management and Adaptation

Abstract: This chapter discusses integrated approaches to the management of risks related to extreme weather and climate change. This is done with the Loss and Damage (L&D) mechanism of the UNFCCC in mind. Relevant insights are provided for climate policy negotiators and policymakers on how risk management and adaptation interact with L&D solutions, and vice versa, on how L&D-related activities can support risk reduction and adaptation in vulnerable countries. Particular attention is devoted to how risk management can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…For adaptation measures, a notable variation was observed in both practice rates and influencing factors across the different local contexts within the prefectures. This result is in line with those of previous studies that have focused on regional characteristics, where many studies on adaptive behavior have emphasized risk management at the local community level (Wouter Botzen et al, 2019) or have found that place attachment, including the local community, has influenced adaptive behavior (van Valkengoed and Steg, 2019). However, most direct regional comparisons on adaptation so far have been comparisons on local government regional adaptation plans (Baba et al, 2017).…”
Section: Pathsupporting
confidence: 88%
See 1 more Smart Citation
“…For adaptation measures, a notable variation was observed in both practice rates and influencing factors across the different local contexts within the prefectures. This result is in line with those of previous studies that have focused on regional characteristics, where many studies on adaptive behavior have emphasized risk management at the local community level (Wouter Botzen et al, 2019) or have found that place attachment, including the local community, has influenced adaptive behavior (van Valkengoed and Steg, 2019). However, most direct regional comparisons on adaptation so far have been comparisons on local government regional adaptation plans (Baba et al, 2017).…”
Section: Pathsupporting
confidence: 88%
“…Therefore, natural disaster risk reduction measures at the individual and household levels can contribute to climate change adaptation. Integrated risk management has also been proposed to reduce the risk of community residents under climate change (Wouter Botzen et al, 2019). Several examples of specific disaster risk behaviors are reported (Grothmann and Reusswig, 2006); however, measures related to climate change adaptive behavior, often address only specific issues, such as agricultural measures for farmers (Arbuckle et al, 2015;Dang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a replication of the National Comorbidity Survey with 6,483 adolescents and their parents, McLaughlin et al (2013) found a 61.8% lifetime prevalence of exposure to a potentially traumatic event, and a 7.6% lifetime conditional prevalence of PTSD given such exposure. In addition, the number of individuals repeatedly and sometimes continuously exposed to trauma of all types, such as child abuse, mass shootings, natural and weather-related disasters, pandemics, systemic discrimination, harassment, and assault based on gender and race, hate crimes, and refugee and asylum crises, has increased markedly in recent years (Fox & DeLateur, 2014; Sutton, 2019; Wouter Botzen et al, 2019).…”
Section: The Need For Trauma Trainingmentioning
confidence: 99%
“…Extreme weather is expected to be even more influential in vulnerable areas where food security is not perceived to be a presumed convenience (Wheeler, 2013, UNICEF, 2022. The impact of natural hazards is of strong influence in low-income countries, where direct losses are generally higher than in high-income ones (Botzen et al 2019). However, also at country scale, vulnerability assessments may overlook significant urban-rural differences, necessitating the future development of detailed vulnerability curves to accurately simulate storm damages and account for variations in exposure and vulnerability across regions (Baldwin, 2023).…”
Section: Vulnerability Of Banana Production Systemsmentioning
confidence: 99%